Institutionalization of health technology assessment in the peruvian health system - Castro-Reyes, Maribel Marilú (2022)
Health technology assessment (HTA) is a tool that contributes to making informed decisions, the efficient use of financial resources and, above all, to providing effective and safe health technologies. In 2016, a proposal was made to create a health technology assessment institution in the Peruvian health system with a national scope that promotes the implementation of the most appropriate health policies, benefits or interventions. To date, regulations have been issued that position the HTA as part of the decision process for financing health technologies for the management of rare or orphan diseases and oncological diseases in the Peruvian health system; however, the organizational adjustments that materialize its institutionalization have not been made. This article addresses the institutionalization of STD in the Peruvian health system based on the persistent need for informed decision-making, the institutionalization proposal developed in 2016 and the current legal framework.